Transparency in financial reporting: Is country-by-country reporting suitable to combat international profit shifting? - Maria Theresia Evers; Ina Meier; Christoph Spengel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Aggressive tax planning efforts of highly profitable multinational companies (Base Erosion and Profit Shifting (BEPS)) have recently become the subject of intense public debate. As a response, several international initiatives and parties have called for more transparency in financial reporting, especially by means of a country-specific reporting of certain tax information (Country-by-Country Reporting (CbCR)). In our paper, we demonstrate that neither consolidated nor individual financial accounts seem to be an appropriate platform to provide such country-specific information and, therefore, that CbCR cannot be based on extended financial accounting standards. Moreover, we argue that even separate CbCR templates do not prevent multinationals from profit shifting, since their common tax minimization strategies are mainly based on the legal exploitation of gaps and loopholes in national and international tax law. In that regard, we show that expected costs for CbCR would exceed expected benefits and therefore contend that CbCR cannot be regarded as a convincing measure to combat international profit shifting. Instead, we argue that tax legislators should limit profit shifting by enforcing national and international tax rules and by closing gaps in tax law. In particular, we call for more tightened and standardized transfer pricing regulations to be adopted at an international level.
Keywords: H20; H26; F23; K34; M41; 330; tax avoidance; profit shifting; multinational firms; tax reform; tax reporting; country-by-country reporting; international transfer pricing